A Comparative Study Between Diclofenac Sodium and Diclofenac Sodium-Paracetamol Combination in The Pain Management of Adult Post-Tonsillectomy Patients (KYAMC Journal, 2026)
Background: Tonsillectomy is one of the most common surgical procedures performed in adults which is associated with severe postoperative pain. Inadequate analgesia in the post-tonsillectomy period may result in poor oral intake, dehydration, sleep deprivation. In moderate to severe pain, multimodal analgesia has been used where different type of analgesics are used in combination to get adequate pain relief.Objective: To compare the analgesic efficacy of NSAIDs versus NSAIDs combined with paracetamol in managing postoperative pain following tonsillectomy in adults.Material and Methods: This prospective study was carried out in 100 patients above 18 years who underwent tonsillectomy from October 2024 to September 2025 in Khwaja Yunus Ali Medical College Hospital. Patients were equally divided into two groups: Group A got Diclofenac (Nopain) alone, while Group B received a combination of Diclofenac (Nopain) and Paracetamol (Napa) as analgesics postoperatively. Both groups got the medication three times daily, with rescue medication (Diclofenac sodium suppository) given as needed. The intensity of pain was measured using a numeric pain rating scale, ranging from 0 to 10, and the mean pain score of each group was calculated at second and ninth postoperative day and the data was analysed and recorded.Results: Among 50 patients in each group, 32 patients were male and 18 were female in Group A, while 27 were male and 23 were female in Group B. A maximum of the patients, which was 33 in Group A and 26 in Group B, were in between 6 to 12 years of age.  For both groups, mean pain score was measured at second and ninth postoperative day. In second postoperative day, the mean pain score of Group A was 5.38 and Group B was 3.98. Z value was 2.74 and P value was < 0.05 which was statistically significant. In ninth postoperative day, the mean score of Group A was 4.54 and Group B was 3. Z value was 2.8 and P value was < 0.05 which was statistically significant. 11 patients in Group A and 5 patients in Group B required diclofenac sodium suppository as a rescue medication for pain relief when the pain was severe.Conclusion: NSAID-Paracetamol combination provides better pain relief while reducing the need for higher doses of NSAIDs     and their associated risks.KYAMC Journal Vol. 16, No. 03, October 2025: 131-134.